Can the Presence of Endoscopic High-Risk Stigmata be Bredicted before Endoscopy? A Multivariable Analysis Using the RUGBE Database - Yen-I Chen; Jonathan Wyse; Alan Barkun; Marc Bardou; Ian M Gralnek; Myriam Martel (Canadian Journal of Gastroenterology and Hepatology)
BACKGROUND: Many aspects in the management of acute upper gastrointestinal bleeding rely on pre-esophagogastroduodenoscopy (EGD) stratification of patients likely to exhibit high-risk stigmata (HRS); however, data predicting the presence of HRS are lacking.